2002
DOI: 10.1109/ted.2002.806790
|View full text |Cite
|
Sign up to set email alerts
|

Impact of lateral source/drain abruptness on device performance

Abstract: This paper presents a detailed study of the impact of lateral doping abruptness in the source/drain extension region and the gate-extension overlap length on device performance. Proper choice of the metric used to compare the different device designs is essential. Series resistance and threshold voltage roll-offs are shown to be incomplete measures of device performance that could lead to inconsistent lateral abruptness requirements. While series resistance is seen to improve with increasing junction abruptnes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(27 citation statements)
references
References 18 publications
0
27
0
Order By: Relevance
“…This problem is even more severe in a DGFET since the presence of two channels implies that twice the current flows through the series resistance, leading to higher potential drop across the extrinsic resistance. Previous work on analysis [9], [10] of extrinsic resistance has been Manuscript received July 23, 2003; revised August 15, 2003 focused on the conventional planar bulk MOSFET structure. In [10], the authors suggest the existence of optimal lateral abruptness of the source/drain extension doping profile.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This problem is even more severe in a DGFET since the presence of two channels implies that twice the current flows through the series resistance, leading to higher potential drop across the extrinsic resistance. Previous work on analysis [9], [10] of extrinsic resistance has been Manuscript received July 23, 2003; revised August 15, 2003 focused on the conventional planar bulk MOSFET structure. In [10], the authors suggest the existence of optimal lateral abruptness of the source/drain extension doping profile.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work on analysis [9], [10] of extrinsic resistance has been Manuscript received July 23, 2003; revised August 15, 2003 focused on the conventional planar bulk MOSFET structure. In [10], the authors suggest the existence of optimal lateral abruptness of the source/drain extension doping profile. It is not clear whether the same results and conclusions would hold for advanced ultrathin body DGFET structures where the process constraints and tunable parameters are quite different.…”
Section: Introductionmentioning
confidence: 99%
“…Further device simulation suggests that with the junction abruptness improved from the original 10dec/nm to the ITRS requested 2.7dec/nm [9] for a 50nm channel length, the peak f T within gate bias of 1.5V can reach as high as 99.4GHz. This corresponds to an almost threegeneration-hop in RF performance that can be ultimately achieved with VMOSFETs using a 0.35µm lithography stepper if ultra abrupt junctions are achieved by advanced annealing techniques.…”
Section: Ekv Modellingmentioning
confidence: 99%
“…For example, the short channel effects have been found to be independent of the junction depth Yj and simulation results showed that IoN increases significantly with the increase in Yj [6]. Additionally, a detailed study of the impact of lateral doping abruptness of SDE on device's ION and IOFF was presented in [7] and proposed some design guidelines for the SDE. Also, leakage currents have been shown to be more sensitive to the variations in T0,o Halo doping profile (Nhalo, lC), and Lg [4].…”
Section: Problem Definitionmentioning
confidence: 99%